2020
DOI: 10.24940/ijird/2020/v9/i1/jan20069
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Perceived Difficult Concepts in Geometry by Pre-Service Teachers of E. P. College of Education, Bimbilla, Ghana

Abstract: The kind of teaching methods adopted by teachers, teacher zeal and commitment and the pace and level at which lessons are presented go a long way to influence perception of difficult topics. Mathematics is a body of knowledge, skills, and procedures that can be used in a rich variety of ways: to describe, illustrate, interpret, predict and to explain patterns and relationships in number, algebra, shape and space, measurements and data. Concepts in mathematics are interrelated and have interconnected elements. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
5
0
3
Order By: Relevance
“…Penguasaan guru terkait materi ajar merupakan salah satu faktor penentu kualitas pembelajaran dan hasil belajar siswa (Robichaux-Davis & Guarino, 2016 pembelajaran. Idris menyatakan bahwa kegagalan guru menggunakan strategi pembelajaran yang sesuai menjadi salah satu penyebab peserta didik gagal memahami konsep geometri dan gagal mengembangkan keterampilan pemecahan masalah geometri (Novita et al, 2018;Salifu et al, 2018).…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Penguasaan guru terkait materi ajar merupakan salah satu faktor penentu kualitas pembelajaran dan hasil belajar siswa (Robichaux-Davis & Guarino, 2016 pembelajaran. Idris menyatakan bahwa kegagalan guru menggunakan strategi pembelajaran yang sesuai menjadi salah satu penyebab peserta didik gagal memahami konsep geometri dan gagal mengembangkan keterampilan pemecahan masalah geometri (Novita et al, 2018;Salifu et al, 2018).…”
Section: Pendahuluanunclassified
“…Salah satu teori pembelajaran dalam geometri yang banyak digunakan untuk mengembangkan pembelajaran geometri yang efektif ialah Teori Van Hiele (Salifu et al, 2018). Van Hiele menyatakan bahwa kemampuan berpikir geometri peserta didik berkembang dalam lima tingkatan selama proses belajar.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…The above narratives offer reasonable grounds for mathematics educators to begin paying attention to PST students' geometry preparation in Ghanaian context where only 27% of basic school teachers are said to inspire mathematical reasoning (Keaveney et al, 2018) and where research studies and national examinations results have indicated the struggle in geometry studies by both senior high school (SHS) students (West Africa Examination Council [WAEC], 2015, 2017a and PST students (Armah et al, 2017;Armah & Kissi, 2019;Salifu et al, 2018; University of Cape Coast-Institute of Education [UCC-IOE], 2011,2012,2013,2014). The narrative is not very different with the basic education certificate examinations (BECE) candidates.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies report that van Hiele's geometric thinking is important to improve, especially for prospective teacher students (Armah et al, 2017(Armah et al, , 2018Armah & Kissi, 2019;ERDOGAN, 2020;Salifu et al, 2018;Yılmaz & Koparan, 2015). Research reported how to improve van hiele's geometric thinking without paying attention to aspects of soft skills.…”
Section: Introductionmentioning
confidence: 99%